Agomelatine modulates calcium signaling through protein kinase C and phospholipase C-mediated mechanisms in rat sensory neurons - Serhatlioglu, Ihsan; Bilgin, Batuhan; Kacar, Emine; Ozcan, Sibel; Canpolat, Sinan; Ayar, Ahmet; Ozcan, Mete (Wiley, 2019)
Agomelatine, a novel antidepressant exerting its effects through melatonergic and serotonergic systems, implicated to be effective against pain including neuropathic pain but without any knowledge of mechanism of action. To explore the possible role of agomelatine on nociceptive transmission at the peripheral level, the effects of agomelatine on intracellular calcium ([Ca2+](i)) signaling in peripheral neurons were investigated in cultured rat dorsal root ganglion (DRG) neurons. Using the fura-2-based calcium imaging technique, the effects of agomelatine on [Ca2+](i) and roles of the second messenger-mediated pathways were assessed. Agomelatine caused [Ca2+](i) signaling in a dose-dependent manner when tested at 10 and 100M concentration. Luzindole, a selective melatonin receptor antagonist, almost completely blocked the agomelatine-induced calcium signals. The agomelatine-induced calcium transients were also nearly abolished following pretreatment with the 100ng/ml pertussis toxin, a Gi/o protein inhibitor. The stimulatory effects of agomelatine on [Ca2+](i) transients were significantly reduced by applications of phospholipase C (PLC) and protein kinase C (PKC) blockers, 10M U73122, and 10M chelerythrine chloride, respectively. The obtained results of agomelatine-induced [Ca2+](i) signals indicates that peripheral mechanisms are involved in analgesic effects of agomelatine. These mechanisms seems to involve G-protein-coupled receptor activation and PLC and PKC mediated mechanisms.
Keywords: agomelatine; antidepressant; calcium signaling; nociception; sensory neurons